Comparison of oral versus intravenous tranexamic acid in total knee and hip arthroplasty: A GRADE analysis and meta-analysis - Sun, Changjiao (Medicine (Baltimore), 2020)
BACKGROUND: The efficacy and safety of oral tranexamic acid (TXA) remain controversial because of the small number of clinical studies. The aim of the present study was to compare the efficacy and safety of oral TXA with intravenous TXA in patients undergoing total hip arthroplasty and total knee arthroplasty in a systematic review and meta-analysis. METHODS: We conducted a meta-analysis to identify randomized controlled trials (RCTs) involving oral and intravenous TXA in total hip arthroplasty and total knee arthroplasty up to December 2019 by searching databases including PubMed, Web of Science, Embase, the Cochrane Controlled Trials Register, the Cochrane Library China Biology Medicine, China National Knowledge Infrastructure, China Science and Technology Journal Database and Wanfang. The mean difference or standard mean difference was used to assess continuous outcomes such as hemoglobin (Hb) drop, total blood loss, drain blood loss, and length of hospital stay, with a 95% confidence interval. Relative risks with a 95% confidence interval were used to assess dichotomous outcomes such as transfusion rate and the incidence of deep venous thrombosis and calf muscular vein thrombosis. Review Manager was used for the meta-analysis. RESULTS: Ten RCTs containing 1080 participants met the inclusion criteria. We found no significant differences in terms of the average Hb drop (P = .60), total blood loss (P = .60), transfusion rate (P = .99), drain blood loss (P = .91), length of hospital stay (P = .95), and the incidence of deep venous thrombosis (P = .55) and calf muscular vein thrombosis (P = .19) between oral and IV TXA. CONCLUSIONS: Compared with the IV TXA, oral TXA has similar effects on reducing the Hb drop, total blood loss, transfusion rate, drain blood loss, and length of hospital stay without increasing the risk of calf muscular vein thrombosis and deep venous thrombosis. Furthermore, oral TXA is easy to access and administer, which decreases the workload of nurses and even delivers cost-saving benefits to the health care system. We thus conclude that oral TXA may be an optimal approach in total joint arthroplasty. However, more high-quality and multicenter RCTs are still needed to confirm our conclusions. REGISTRATION: The current meta-analysis was registered on PROSPERO (International Prospective Register of Systematic Reviews), and the registration number was CRD42018111291.